Managerial judging and alternative dispute resolution in Australia: an example for South Africa to emulate? (Part 1) - De Vos, Wouter; Broodryk, T. (Juta & Company Ltd. * Juta Law, 2017)
The English common law heritage of the states and territories in Australia (most of which were former British colonies) ensured that these different jurisdictions all embraced the adversarial system of civil litigation.1 Essentially, this meant that a passive role was accorded to the judge, especially during the pre-trial phase, while the parties, through their lawyers, played an active role during both the pre-trial and trial stages. By virtue of the principle of party control the parties were in charge of preparing their cases for trial and presenting their evidence and arguments at the trial. During the pre-trial phase the judge would react only if a party sought interlocutory relief, and even during the trial the judge assumed the role of a passive arbitrator, only ensuring that the lawyers conducted themselves in a seemly manner and complied with the “rules of the game”.